Targeting SARM1 improves autophagic stress-induced axonal neuropathy - Kim, Hye Ran; Lee, Hye Jin; Jeon, Yewon; Jang, So Young; Shin, Yoon Kyoung; Yun, Jean Ho; Park, Hye Ji; Koh, Hyongjong; Lee, Kyung Eun; Shin, Jung Eun; Park, Hwan Tae (TAYLOR & FRANCIS INC, 2024)
Macroautophagy/autophagy, a lysosome-dependent self-degradative process, is a critical mechanism for the clearance of misfolded proteins and dysfunctional organelles in neurons. In the peripheral nervous system, autophagic stress is associated with the development of peripheral neuropathy. However, the molecular mechanism of axonal neuropathy induced by autophagic stress due to dysfunction of autophagy in peripheral neurons in vivo is still unclear. We found that dorsal root ganglion (DRG) neuron-specific atg7 (autophagy related 7) knockout (atg7-cKO) mice employing two different Cre recombinase systems exhibited sensory neuropathy approximately 2 months after birth. In electron microscopy analysis, axon degeneration was clearly observed in the myelinated fibers of the sciatic nerve before the appearance of neuronal cell death. Dystrophic axons filled with abnormal vesicular accumulations and amorphous inclusions were specifically localized in the myelinated axons within the DRG in atg7-cKO mice, indicating the presence of autophagic stress in proximal axons. In line with the EM findings, the mutant mice showed preferential induction of axonal injury-associated genes, including ATF3 (activating transcription factor 3), in large-size DRG neurons that constitute myelinated fibers without axotomy. SARM1 (sterile alpha and HEAT/Armadillo motif containing 1), the central executioner of Wallerian degeneration, was activated in the sciatic nerves of atg7-cKO mice, and axonal degeneration and sensory neuropathy in atg7-cKO mice were prevented via expression of a dominant-negative Sarm1 transgene. Our findings demonstrate the importance of SARM1-dependent axon degeneration in the development of peripheral sensory neuropathy induced by impairment of autophagy.